Rare metastasis to paranasal sinuses from triple-negative breast cancer: A case report and literature review. Issue 47 (November 2017) - Xiong, Jie; Chen, Jing; Zheng, Liduan; Yang, Shengli; Zhao, Guifang; Cheng, Jing
Abstract: Rationale: Breast cancer, the most common form of cancer among women, rarely metastases to the head and neck region. To date, there have been only 6 similar cases in the literature, and most patients in these reports had very poor prognosis. Patients concerns: We report a 61-year-old female presented pain and numbness on the right side of the face 5 years after being diagnosed with triple-negative breast cancer. Diagnosis: Magnetic resonance imaging (MRI) revealed a tissue mass in the sphenoid sinus. The tissue biopsy confirmed metastasis of breast cancer. Intervention: The patient received initial chemotherapy and radiotherapy plus 10 cycles of maintenance chemotherapy Outcomes: The patient got long-term progression-free survival time. The total time to progression was 32 months. Lessons: Although breast cancer rarely metastasizes to the head and neck region, awareness should be raised when breast cancer patients experience headache or have sinus-related symptoms. Chemotherapy and radiotherapy may be effective to treat paranasal sinus metastasis of triple-negative breast cancer, and patients may achieve long-term survival.